Food insecurity and ART adherence in Swaziland: the case for coordinated faith-based and multi-sectoral action. Issue 5 (4th July 2017) - van Wyngaard, Arnau; Root, Robin; Whiteside, Alan
ABSTRACT: Faith-based organisations (FBOs) have long been involved in HIV and AIDS impact mitigation and humanitarian relief, but most are not equipped to intervene in the structural drivers of food insecurity and attendant health inequities. Acknowledging limitations is as paramount a task for organisational effectiveness as maximising strengths. This article reports findings from a study of HIV-positive care supporters who volunteer with a church-run home-based care organisation in Swaziland. The article seeks to assess the impact of chronic food insecurity on antiretroviral adherence practices and how these individuals manage daily food shortages. Findings highlight the limited capacities of FBOs in highly vulnerable settings and the imperative for international and governmental coordination.